Exogenous carbonaceous microstructures in Early Archaean cherts and BIFs from the Isua Greenstone Belt: implications for the search for life in ancient rocks - Westall, F.; R.L., Folk (Precambrian Research, 2003)
The microstructure of HF-etched samples of Early Archaean banded iron formations (BIFs) and cherts from the >3.7 b.y.-old Isua Greenstone Belt (southwestern Greenland) was investigated using high resolution scanning electron microscopy equipped with an electron diffraction system, capable of analysing light elements. The rocks contain both endogenous (of internal origin) and exogenous (of external origin) carbonaceous microstructures. The former consist of inclusions of graphite and, possibly, small, amorphous carbonaceous particles, both embedded in metacherts (however, further in situ TEM studies are needed to verify the endogeneity of the amorphous particles). Moreover, these rocks also contain endolithic microorganisms (i.e. inhabiting cracks in rocks), as well as undifferentiated carbonaceous matter, that occur in fractures and cracks between grains. The microorganisms include cyanobacteria, filamentous microorganisms such as fungal hyphae and possibly bacteria, as well as large, unidentified cells or spores. Most of the microorganisms appear to have been fossilised. The endoliths are evidently younger than the host rock, but must have infiltrated at different periods, most likely after the Inland Ice retreated (~8000 years ago).The presence of endolithic carbonaceous matter in cracks and microfissures in these rocks will affect any analyses of bulk samples, such as carbon isotopes and chemical biomarkers, as well as analyses of acid-macerated residues. Thus, previous isotope measurements made on BIFs and cherts from Isua may reflect younger contamination rather than an endogenous (original) signal. Likewise, some of the previously described Isuan microorganisms probably represent recent, endolithic contamination.